Adolescent Deaths - Tüzün, Birgül; Sözen, Mehmet Şevki; Dokgöz, Halis; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 1997)
This study was aimed to find out the examination of adolescent deaths included in forensic cases and the effects of behavior peculiarities of this period on the cause and origin of deaths. 564 cases aged 11-20 years autopsied at the Morgue Department of İstanbul, Turkey in 1994-96 were examined. In 534 cases, the cause of death was determined and included in the study, but 26 cases left outside of this study because the cause of death was not determined. The 76.8 percent of the 538 cases was males and 23.2 percent was females. Accidental deaths(%4l.3) occupied the majority of the adolescent deaths. Homicidal deaths(%36.2) and suicidal deaths (%17.6) were the other origins of deaths. Manner of death'was not determined in 25 cases. Unnatural deaths (%93-l) were found to be the most common cause of death. Firearm deaths (%18.4) occupied the majority of all unnatural deaths. The following causes of unnatural deaths were stab and incised wounds (%14.8) and hanging (%13.6). The results demonstrated that the causes of adolescent deaths in forensic cases almost reflected the violence based behavior pecularities of this age group.Key Words: Child, Adolescent, Violence, Death.
Keywords: child; adolescent; violence; death